Introduction to the special issue. - Wiley, Jennifer; Wolfe, Michael B.; Britt, M. Anne (Discourse Processes)
This special double issue of Discourse Processes highlights work presented at the 34th annual meeting of the Society for Text & Discourse held in Chicago in July 2024. The conference provided an occasion to celebrate the life and contributions of Walter Kintsch. As a special addition to this issue, we have the privilege of including a reflection on the field written by Walter himself. The other contributions represent the breadth of topics researched by the interdisciplinary and international membership of the Society, with papers coming from both text and discourse traditions. Three papers looking at text processing consider reading processes at a variety of grain sizes. Three papers exploring discourse also cover a range of topics from face-to-face interactions to social media posts.